ITF Taekwon-Do pedagogy in North Korea: A case study (Revista de Artes Marciales Asiáticas, 2019)
Background. Despite the style of Taekwon-Do taught by the International Taekwon-Do Federation (ITF) being founded in the Republic of Korea (ROK; South Korea), it is known predominately as “North Korean Taekwon-Do.” Problem and Aim. Taekwon-Do was introduced to the People’s Democratic Republic of Korea (DPRK; North Korea) in 1980, but since then no studies have reported how it is practiced in that country due to the DPRK government’s restricting access to its populace. This research aims to begin establishing if there are differences in pedagogical purpose and praxis in DPRK Taekwon-Do. Methodology. An internet search for individuals who traveled to the DPRK to practice Taekwon-Do specifically was conducted. A systematic literature of ITF pedagogical materials was performed, and a multipurpose, qualitative questionnaire was implemented. Out of the seven individuals who were identified and contacted, two agreed to participate in the current study; however, one of those two were disqualified due to incorrectly completing the questionnaire. A descriptive, non-experimental case study of one subject (Singaporean female aged 36 yr.) was then conducted. A qualitative analysis of the data resulting from the questionnaire and follow-up interviews was performed. Results. All five areas of the ITF’s curriculum (i.e., fundamental techniques, tul [forms], sparring, dallyon [forging or conditioning of the body], and self-defense) and the three levels of Taekwon-do’s pedagogy (i.e., musul [martial technique], muyae [martial artistry], and mudo [martial way]) were found in DPRK Taekwon-Do. Discussion and Conclusions. Despite the severe limitations of being unable to interview DPRK Taekwon-Do practitioners directly and the smallest small sample group possible, it was learned that DPRK instructors most likely teach all aspects of General Choi’s Composition of Taekwon-Do, and the stratified Taekwon-Do pedagogy theory was found in the subject’s practice in the DPRK.